Impact of hypertensive disorders of pregnancy on neonatal outcomes among infants born at 24+0–31+6 weeks’ gestation in China: A multicenter cohort study - Ge, Jianfang; Gu, Xinyue; Jiang, Shanyu; Yang, Ling; Li, Xiaoyan; Jiang, Siyuan; Jia, Beibei; Chen, Caihua; Cao, Yun; Lee, Shoo; Zhao, Xiaopeng; Ji, Yong; et al. (Frontiers in Pediatrics, 2023)
Objective To describe the rate of hypertensive disorder of pregnancy (HDP) among mothers of very preterm infants (VPIs) admitted to Chinese neonatal intensive care units (NICUs), and to investigate the relationship between HDP and the outcomes of VPIs. Study design Cohort study of all VPIs born at gestational age of 24+0-31+6 weeks and admitted to 57 tertiary NICUs of the Chinese Neonatal Network (CHNN) in 2019. Infants with severe congenital anomalies or missing of maternal HDP information were excluded. Two multivariate logistic regression model were generated to assess the relationship between HDP and neonatal outcomes. Results Among 9262 infants enrolled, 1744/9262 (18.8%) infants were born to mothers with HDP，with an increasing incidence with increasing gestational age. VPIs born to mothers with HDP had higher gestational age but lower birth weight and were more likely to be small for gestational age. Mothers with HDP were more likely to receive antenatal steroids, MgSO4 and cesarean section. Infants in HDP group showed higher observed rates of mortality or any morbidity than infants in non-HDP group (50.2% vs 47.2%, crude OR 1.13, 95% CI 1.02 to 1.26). However, the associations of HDP and adverse outcomes were not significant after adjustment. In HDP group, mothers of 1324/1688 (78.4%) infants were diagnosed with preeclampsia/eclampsia. Infants born to mothers with preeclampsia/eclampsia had significantly lower odds of early death and severe ROP. Conclusions Near one fifth of VPIs were born to mothers with HDP in Chinese NICUs. No significant association was identified among HDP and adverse neonatal short-term outcomes of VPIs, while long-term follow-up of theses infants are needed.